Índice de sustentabilidade para coleta seletiva no município de Aracaju / SE - Dantas, José Henrique Leal (2019)
The National Solid Waste Policy (PNRS), Federal Law No. 12.305 / 2010, is a challenge for municipal public management throughout the country, as it provides for guidelines on integrated solid waste management, responsibilities of generators, government and applicable economic instruments, as well as tools for optimizing all these factors. In this context, this research sought to evaluate the sustainability index for selective collection as a tool for improving integrated solid waste management for the municipality of Aracaju / SE. To this end, a bibliographic research was conducted by consulting books, articles and specialized reports in the area of solid waste, analyzing and describing the research scenario, and the use of environmental, social, economic and institutional sustainability indicators to purposes of determining a sustainability index for the city of Aracaju / SE. The research found that the Aracaju Municipality has a sustainability index of 2.5 (two point five), considered low because of the lack of integrated public policies for the use of selective collection.